An in-depth interview study of women's perspectives on the effects of contraceptive use on future fertility in Ethiopia and Kenya - Kristen Kirksey; Hanna Feleke; Sarah Okumu; Hailemichael Bizuneh; Pauline Wekesa; Lauren Suchman; Beth Phillips; Zachary Kwena; Jenny Liu; Elizabeth Bukusi; Serah Gitome; Ewenat Gebrehanna; et al. (SSM: Qualitative Research in Health)
Infertility is a common perceived side effect of contraceptive use among women in sub-Saharan Africa, and fear of infertility can affect contraceptive choices. While no choice is inherently negative, it is critical that women have accurate information about side effects to ensure contraceptive decision-making agency. Despite the prevalence of infertility fears, little is known about women's specific beliefs, where they originate, and how they inform contraceptive decisions. We sought to fill this gap in Kenya and Ethiopia through in-depth interviews with women aged 15–45 in Nairobi and Kisumu, Kenya, and Addis Ababa and North Shoa Zone of Amhara Region, Ethiopia (N = 83). We utilized a modified grounded theory approach for data collection and analysis.While not all participants believed in a link between contraception and infertility, those that did understood several mechanisms. Some, such as delayed return to fertility and aging out of childbearing years, were supported by clinical evidence. Others, such as accumulation of harmful substances in the body, damage to the reproductive system, and negative effects from early or prolonged use, were not supported by clinical evidence. Healthcare providers were a trusted source of information, disseminating information supported and unsupported by clinical evidence. Fear of infertility led women to prefer non-hormonal or short-term methods, avoid methods that cause amenorrhea, or delay use until after having children.Results suggest the need to address side effect misinformation given by providers. Further, the specificity this study offers can inform strategies to improve contraceptive counseling and education campaigns in service of decision-making agency.